2016
DOI: 10.1111/risa.12626
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood and Worrying About Climate Change: The Limitations of Previous Approaches

Abstract: The present study considers the correlation between parenthood and worry about the consequences of climate change. Two approaches to gauging people's perceptions of the risks of climate change are compared: the classic approach, which measures risk perception, and the emotion-based approach, which measures feelings toward a risk object. The empirical material is based on a questionnaire-based survey of 3,529 people in Sweden, of whom 1,376 answered, giving a response rate of 39%. The results show that the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 48 publications
(178 reference statements)
2
33
0
3
Order By: Relevance
“…As pointed out by several authors (e.g., [26,30]), an increase in family size (e.g., having a newborn) might increase pro-environmental concerns, but at the same time might produce a less environmentally friendly lifestyle temporarily due to the fact of, for instance, financial concerns, safety issues, or time constraints. Indeed, previous research shows that an association between parenthood and being worried about the consequences of climate change emerges only when emotional aspects of the risk are measured but not when parents are just required to conduct cognitive-based estimates of the risk [31]. It is thus important to focus more on the psychological mechanisms involved in environmental decision-making in family relations.…”
Section: Can Kin Appeals Save the Environment?mentioning
confidence: 99%
“…As pointed out by several authors (e.g., [26,30]), an increase in family size (e.g., having a newborn) might increase pro-environmental concerns, but at the same time might produce a less environmentally friendly lifestyle temporarily due to the fact of, for instance, financial concerns, safety issues, or time constraints. Indeed, previous research shows that an association between parenthood and being worried about the consequences of climate change emerges only when emotional aspects of the risk are measured but not when parents are just required to conduct cognitive-based estimates of the risk [31]. It is thus important to focus more on the psychological mechanisms involved in environmental decision-making in family relations.…”
Section: Can Kin Appeals Save the Environment?mentioning
confidence: 99%
“…A similar result was found previously by Hamilton () and Lutzenhiser (). Similarly, Ekholm and Olofsson () found that when the survey questions are designed to elicit emotions, parents do worry more about climate change than non‐parents.…”
Section: Theoretical and Empirical Framework And Hypothesesmentioning
confidence: 99%
“…När man ser till omsorg om kommande generationer och de osäkra risker som dessa kan komma att utsättas för, ligger det nära till hands att ur ett omsorgsperspektiv relatera till föräldraskapets betydelse för oro för sådana typer av risker. Föräldraskap, som är nära förknippat med kärlek, omsorg och ansvar, har visat sig påverka individers oro för klimatrisker (Ekholm & Olofsson 2017;Ekholm 2020). Att känna och agera utifrån omsorg om andra påverkar oron för den som omsorgen riktar sig till.…”
Section: Teori Och Tidigare Forskningunclassified
“…Denna känsla av osäkerhet inför framtiden har inverkan på individers omsorg om andra (Groves 2009). Tidigare studier visar även att uppfattningen om att klimatförändringarna kommer med negativa konsekvenser kan ge stora samvetskval och en drivkraft att inte vilja utsätta kommande generationer för skada (Groves 2009; se även Ekholm & Olofsson 2017) De orosbejakande uttrycker även en stor oro för hur det kommer att bli för barnen i framtiden. Berättelserna visar därmed en tydlig moralisk omsorgsoro för kommande generationer och att vi tillsammans, både lokalt och globalt, har ett ansvar att begränsa vår klimatpåverkan.…”
Section: "De Orosbejakande"unclassified
See 1 more Smart Citation